Perbandingan splinting kawat komposit dengan splinting fiber reinforced composite untuk stabilisasi mobilitas gigi - Albert; Purnomo, Racheliza (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Tooth mobility is a periodontal disease accompanied by loss of periodontal ligament attachment and bone destruction. Treatment for stabilization of loose teeth is splinting. The two most commonly used materials are composite wire splinting and fiber reinforced composite splinting. However, there is a dilemma in the community regarding the selection of materials that are more effective for the immobolization of loose teeth. Objective: The purpose of this study was to compare the effectiveness between composite wire splinting and fiber reinforced composites splinting for the stabilization of loose teeth. Methods: The study was conducted using the PRISMA diagram with PubMed, Researchgate, Tripdatabase and Google Scholar databases by searching ("Periodontal Splinting" Or "Wire Splinting" Or "Fiber Reinforced Composite Splinting") And ("Periodontitis"). Results: The initial search showed 385 articles. After removal of duplicates and complete screening of journals for eligibility, the results were 14, and the researcher identified 5 articles that met the criteria for inclusion in this study. Conclusion: Based on the results of the study, it can be concluded that composite wire splinting is more effective than fiber reinforced composite splinting because it effectively reduces tooth mobility and is more stable for loose teeth.